The profit and risk in the interdisciplinary behavior - Fu, Chenbo; Luo, Haogeng; Liang, Xuejiao; Yu, Shanqing (Frontiers in Physics, 2023)
Evaluating the influence of interdisciplinary research is important to the development of science. This work considers the large and small disciplines, calculates the interdisciplinary distance, and analyzes the influence of interdisciplinary behavior and interdisciplinary distance in the academic network. The results show that the risk of interdisciplinary behavior in the large discipline is more significant than the benefits. The peer in the small disciplines will tend to agree with the results of the small discipline across the large discipline. We further confirmed this conclusion by utilizing PSM-DID. The analysis between interdisciplinary distance and scientists' influence shows that certain risks will accompany any distance between disciplines. However, there still exists a "Sweet Spot" which could bring significant rewards. Overall, this work provides a feasible approach to studying and understanding interdisciplinary behaviors in science.